Synthesis of renewable copolyacetals with tunable degradation - Rajput, Bhausaheb S.; Chander, Umesh; Arole, Kailash; Stempfle, Florian; Menon, Shamal K.; Mecking, Stefan; Chikkali, Samir H. (Macromolecular Chemistry and Physics, 2016)
Acetal metathesis copolymerization (AMCP) of renewable isohexide diacetals and aliphatic long-chain diacetals is reported and access to a small family of copolyacetals has been established. Crucial 1-2D NMR and MALDI-ToF-MS findings unambiguously confirm the existence of a copolymeric structure. In a stark contrast to the earlier reported isohexide-polyacetals, the current copolyacetals reveal very slow degradation. Hydrolytic degradation of copolyacetal pellets is extremely slow at pH 7, whereas only 30% degradation over a period of 15 d is observed in 9 M hydrochloric acid solution. GPC investigations reveal that with increasing chain-length the rate of degradation reduces, whereas copolyacetals with short-chain aliphatic segments display a faster degradation profile. The reduced rate of degradation can be attributed to the hydrophobic nature of long-chain acetal segments. In situ NMR spectroscopy reveals the existence of formates, hemiacetals, and diols as degradation products. Thus, the rate of degradation can be tuned by the judicious choice of isohexide-diacetal and linear-diacetals in a copolyacetal.
Keywords: copolyacetals; degradable polymers; diacetals; isohexides; renewable polymers